Proving Learning Outcomes in Mathematic of Long Addition and Subtraction Materials through the Cooperative Learning Type Jigsaw Model Class IB Islamic Elementary School An-Nuriyah - Rosfiani, Okta; Maisyaroh, Maisyaroh; Dasyani , Anita; Aeni , Syafrina Zahratul; Farida, Zulpa (PT. Riset Press International, 2024)
Based on the learning results of first grade students of SDS Ialam An-Nuriyah Jagakarsa South Jakarta, it shows that the results of learning Mathematics about addition and subtraction in long series are still below the specified KKM which is 70. Of the 25 students, only 8 students were able to reach the KKM, while 17 students were declared not to have reached the KKM score. In line with this, an improvement in learning Mathematics about addition and subtraction using the cooperative learning type jigsaw model was carried out. The purpose of this study was to improve the learning outcomes of IB grade students on long addition and subtraction. This research uses a class action research method that uses a cycle system consisting of planning, implementation, observation and reflection. Based on the results of the study, in the pre-cycle students whose learning completeness was above KKM 70 were only 8 students or (36.0%) out of 25 students. In cycle 1 it increased to 14 students or (56.0%) out of 25 students. While in cycle 2 it increased to 24 students or (96.0%) of 25 students. This means that the class learning completeness has been achieved because it has exceeded the target of the predetermined success indicator of 80%. The conclusion is that using the jigsaw type cooperative learning model on long addition and subtraction material can improve student learning outcomes.